2014
DOI: 10.3109/0886022x.2014.899474
|View full text |Cite
|
Sign up to set email alerts
|

Significant benefits after renal transplantation in patients with chronic heart failure and chronic kidney disease

Abstract: RTx may play a role in reversing LV systolic dysfunction. Once thought by many to be a contraindication for renal transplantation, this appears not to be the case. The outcomes between the 2 groups are comparable and transplant is an option for even low EF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Similar experiences have been reported in other single institution studies [96][97][98]. Another single center experience reported that KT patients with baseline mean EF of 35% had similar outcomes to those with normal EF in terms of graft and patient survival, largely due to improvement in EF post-KT [99]. These data suggest that restoration of eGFR and reversal of the uremic milieu may play a role in restoration or improvement of myocardial mechanics and function in patients with preexisting cardiomyopathy.…”
Section: H E a R T F A I L U R E I N T H E K I D N E Y T R A N S P L A N T R E C I P I E N Tsupporting
confidence: 81%
“…Similar experiences have been reported in other single institution studies [96][97][98]. Another single center experience reported that KT patients with baseline mean EF of 35% had similar outcomes to those with normal EF in terms of graft and patient survival, largely due to improvement in EF post-KT [99]. These data suggest that restoration of eGFR and reversal of the uremic milieu may play a role in restoration or improvement of myocardial mechanics and function in patients with preexisting cardiomyopathy.…”
Section: H E a R T F A I L U R E I N T H E K I D N E Y T R A N S P L A N T R E C I P I E N Tsupporting
confidence: 81%
“…We observed that both LV mass and LV dimensions improved following KTX, which is consistent with findings from existing literature on the subject. 23,29,30 As the increased afterload caused by hemodynamic abnormalities in ESKD improves following KTX, the heart begins to remodel. 31 This is what we in our cohort observed with the improvements to LV dimensions and decrease in LV mass.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, several small observational studies have shown that, in certain subsets, kidney transplantation can lead to improvements in LV function and normalization of ejection fraction. 4–9…”
mentioning
confidence: 99%
“…2 However, several small observational studies have shown that, in certain subsets, kidney transplantation can lead to improvements in LV function and normalization of ejection fraction. [4][5][6][7][8][9] Stratifying cardiovascular risk for patients with left ventricular dysfunction remains a challenge that faces cardiologists and nephrologists alike. Protocols for cardiac evaluation vary from center to center‚ and this reflects heterogeneity in society guidelines.…”
mentioning
confidence: 99%